If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1b + 4b = 8b Combine like terms: -1b + 4b = 3b 3b = 8b Solving 3b = 8b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-8b' to each side of the equation. 3b + -8b = 8b + -8b Combine like terms: 3b + -8b = -5b -5b = 8b + -8b Combine like terms: 8b + -8b = 0 -5b = 0 Divide each side by '-5'. b = 0 Simplifying b = 0
| 4x-(3x+8)=-2 | | 2c-3=-15 | | 3(x-2)-2(5x-1)=10 | | -2v-7=-23 | | 8n-15-n^2=0 | | 4-p^2=0 | | -6q=q^2 | | 32x=352 | | 3h-5=10 | | n^2=12n-35 | | t=m+10e | | (-8x-4)=9 | | x+(-20)=-20 | | x+(-20)=-11 | | 0=35+12z-z^2 | | z^2=12z-35 | | 7x+15=10x | | -4q-8=36+4q | | 108+18n+2n^2=0 | | n^2+n+16=0 | | 4c-6+8c=42 | | n^2+3n=40 | | 8x-4=3x+11 | | 16+8x=40x | | 3(x-2)+5(x-3)=15x | | -3z+2=5 | | 50+2x=3x-87 | | 5x^2-9x=18 | | 7x-9=4x+9 | | 7n-5=9n+29 | | N+7=6 | | 3a+2=a-6 |